New Monte Carlo simulation of adsorption of gases on surfaces and in pores: A concept of multibins - Fan, Chunyan; Do, D.; Nicholson, D. (American Chemical Society, 2011)
We introduce a new and effective Monte Carlo scheme to simulate adsorption on surfaces and in pores. The simulation box is divided into bins to account for the nonuniform distribution of particle density, and the new scheme takes into account the state of each bin and allows the maximum displacement length to vary with the bin density. The probability of acceptance of insertion and deletion from a bin depends on the density of the fluid in that bin, rather than on the average density in the whole simulation box. In other words, our scheme is local. We apply this new scheme to a canonical ensemble and a grand canonical ensemble, and because it is based on exchange of particles between bins of different density, we refer to this new method as Multibin Canonical Monte Carlo (Mu-CMC) and Multibin Grand Canonical Monte Carlo (Mu-GCMC). The process of particle exchange within the canonical ensemble makes the new scheme much more efficient, compared to conventional canonical ensemble simulation. We apply the new scheme to a number of adsorption systems to illustrate its potential. © 2011 American Chemical Society.